2000
DOI: 10.1111/j.2042-3306.2000.tb05337.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle thickness and neuron density in the caecum of horses with chronic recurrent caecal impaction

Abstract: Summary In this study, the hypothesis that caecal smooth muscle layers would be thinner and the linear neuron density of myenteric plexus greater was tested in normal horses compared to those with chronic recurrent caecal impaction. Four normal horses and 18 horses with chronic recurrent caecal impaction were subjected to euthanasia and 7 tissue samples were collected from each horse at different regions of the caecum (apex, dorsal body, cranial base, dorsal base, caudal base, caudal body, ventral body). Twelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 5 publications
0
27
0
Order By: Relevance
“…If the change observed is primary, it does beg the question as to whether certain animals are predisposed to developing signs of colic and ileus because of this characteristic. As mentioned above, it has been suggested that the reduction in enteric neurons in horses with chronic large intestinal lesions may be a predisposing cause of colic in these animals (Schusser and White, 1997;Schusser et al, 2000). Conversely, in the horse study of Pavone et al (2012), it was suggested that the enteric nervous system and ICC changes observed may have been secondary to the colic episodes.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…If the change observed is primary, it does beg the question as to whether certain animals are predisposed to developing signs of colic and ileus because of this characteristic. As mentioned above, it has been suggested that the reduction in enteric neurons in horses with chronic large intestinal lesions may be a predisposing cause of colic in these animals (Schusser and White, 1997;Schusser et al, 2000). Conversely, in the horse study of Pavone et al (2012), it was suggested that the enteric nervous system and ICC changes observed may have been secondary to the colic episodes.…”
Section: Discussionmentioning
confidence: 95%
“…However, there were two horses with a large colon obstructive disorder (left and right large colon displacement, respectively) that did have a marked reduction in PGP 9.5 immunoreactivity. Interestingly, one of these horses had a history of previous colic episodes including surgery (for the same lesion, a right large colon displacement) and it seems reasonable to speculate that this could be part of the disease process as proposed by Schusser et al (2000). These two horses also had a significant reduction in ICC density that could also have contributed to the motility problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are, however, reports of neuropathies associated with intestinal dysfunction in horses, including equine grass sickness (Scholes et al, 1993;Cottrell et al, 1999), impactions, displacements and volvulus/torsion of the large colon (Schusser et al, 1997) and chronic recurrent caecal impaction (Schusser et al, 2000).…”
mentioning
confidence: 99%